2021
DOI: 10.3389/fpsyg.2021.775308
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Functional Lateralization From the Perspective of Clinical Neuropsychology

Abstract: Objective: The cerebellar functional laterality, with its right hemisphere predominantly involved in verbal performance and the left one engaged in visuospatial processes, has strong empirical support. However, the clinical observation and single research results show that the damage to the right cerebellar hemisphere may cause extralinguistic and more global cognitive decline. The aim of our research was to assess the pattern of cognitive functioning, depending on the cerebellar lesion side, with particular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…The Addenbrooke's Cognitive Test ACE III and the Pathway Test TMT were used to assess cognitive function in 31 patients with localized cerebellar lesions and 31 healthy volunteers. It was discovered that patients with left-sided cerebellar lesions were impaired in the attention and visuospatial domains, while patients with right-sided cerebellar damage had deficits in general cognitive function (Starowicz-Filip et al, 2021). The research by Baillieux also confirmed that the left cerebellum controlled attention and 10.3389/fnhum.2023.1197459 visuospatial skills, but it was also thought that the right cerebellar hemisphere influenced logical thinking and language processing skills (Baillieux et al, 2010).…”
Section: The Cytological Basis Of the Cerebellum And Its Anatomical F...mentioning
confidence: 99%
“…The Addenbrooke's Cognitive Test ACE III and the Pathway Test TMT were used to assess cognitive function in 31 patients with localized cerebellar lesions and 31 healthy volunteers. It was discovered that patients with left-sided cerebellar lesions were impaired in the attention and visuospatial domains, while patients with right-sided cerebellar damage had deficits in general cognitive function (Starowicz-Filip et al, 2021). The research by Baillieux also confirmed that the left cerebellum controlled attention and 10.3389/fnhum.2023.1197459 visuospatial skills, but it was also thought that the right cerebellar hemisphere influenced logical thinking and language processing skills (Baillieux et al, 2010).…”
Section: The Cytological Basis Of the Cerebellum And Its Anatomical F...mentioning
confidence: 99%
“…It is also possible to speculate that the observed asymmetric cerebellar atrophy may be related to speech abnormalities, as studies on functional lateralization of the cerebellum indicate the role of the right cerebellar hemisphere in language and speech processing. 47 Several study limitations need to be mentioned. First, quantitative assessment of clinical severity was not available for most patients, precluding clinical phenotype and brain-morphometry correlation analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One may speculate that abnormal development of cerebellar and cortical motor circuits underlies developmental stutter in LOTS patients. It is also possible to speculate that the observed asymmetric cerebellar atrophy may be related to speech abnormalities, as studies on functional lateralization of the cerebellum indicate the role of the right cerebellar hemisphere in language and speech processing 47 …”
Section: Discussionmentioning
confidence: 99%
“…( 1 , 22 , 23 ). Some studies have also shown that the cerebellum may show laterality in cognition; that is, the left cerebellum is mainly related to visuospatial function ( 24 ), while the right cerebellum is mainly related to executive function ( 25 ).…”
Section: Discussionmentioning
confidence: 99%